Trends of Anger and Physical Aggression in Russian Women During COVID-19 Lockdown - Klimovich-Mickael, Alexandra; Kubick, Norwin; Milanesi, Elena; Dobre, Maria; Łazarczyk, Marzena; Wijas, Baraba; Sacharczuk, Mariusz; Mickael, Michel-Edwar (Frontiers in Global Women's Health, 2021)
The effect of social lockdown during the COVID-19 outbreak on female aggressiveness is not well known. The strict measures of lockdown have resulted in millions of people, worldwide, confined to their homes during the pandemic. However, the consequence of lockdown strategies on females' psychological status including aggressiveness has not yet been investigated. We conducted a cross-sectional study on 31 Russian females' homemakers who are participants in an online fitness platform to investigate the immediate anxiety, depression, and aggression experienced under strict lockdown measures. The participants were surveyed using the hospital anxiety depression scale (HADS) and the Buss-Perry Aggression Questionnaire. We used descriptive and statistical methods to investigate the prevalence of these emotions among two age groups (20–35 and 36–65 years). We found that moderate anxiety prevalence was 77.4% in the entire group while mild depression was 54.8%. Interestingly, the whole sample showed a high level of angriness (p = 0.0002) and physical aggression (p = 0.019). These two emotions seem to be more prevalent than other negative emotions such as hostility, verbal aggression. This relationship was not dependent on age. Overall, there is a significant worsening in female aggression that could lead to higher chances of female victimization and being subjected to partner violence. Future policies designing lockdown strategies should consider this effect on active female homemakers. Due to the small size of our cohort, our results are only indicative of data trends. Larger studies are still needed to confirm the current findings.